READING OF BLIND STUDENTS - Sevala Tulumovic; Aida Bacic-Mujagic (Human Research in Rehabilitation, 2023)
The aim of the research was to determine the success of reading Braille graphemes and understanding the read text in congenitally blind students. The research included 61 students: 30 congenitally blind students, 31 students who went blind later in life, aged 7-18, both genders who are in education and rehabilitation in the Centre for Blind and Visually Impaired Children and Youth Nedzarici in Sarajevo and in elementary schools in Tuzla Canton and Brcko District. The obtained results showed that there is no statistically significant difference in the ability to read Braille graphemes, and a statistically significant difference was shown in the understanding of the read text in Braille between congenitally blind students and students who went blind later in life.